Kata Makian Pele dalam Interaksi Masyarakat Merauke - Narahawarin, Margaretha F. (Kajian Linguistik, 2017)
This research will identify, classiy, and analyze swearwords of Pele that are used in theÂ  interaction of Merauke society. The data has been collected from interviews society Marind and society non Marind to get positive response about swearwords ofÂ  Pele. Moreover, the data has been collected from expressionthe used in communication. Theorise used in this research is the theory form swearword by Wijana and Romadi, the theory functions of using swearwords by Andersson, and the theory shifts of meanings by Simatupang.The result of this research shows that the form of swearwords are in form words, phrases, interjections, vocals, and acronyms. It was found that there are 26 function of using swearwords, namely praise, amazed, expressed hope, as seduction, as a statement, to ask, as a joke or a joke, as a greeting, expresses regret, express a sense of disappointment, expressing astonishment, shock, surprisingly, insulting, offensive, complain, complained repeatedly, extrude, harm or disrupt, threatening, blow up, express extreme emotion, express emotions indirectly, reveals unexpected pain, express feelings of frustration or annoyance, strengthen one's argument. And to the shifts of meanings there are shifts from generic meaning to specific meaning, and shifts of meaning as culture aspect.Keywords: : Swear Words of Pele, Interaction, Merauke Society